Aqueous Photoelectrochemical CO2 Reduction to CO and Methanol over a Silicon Photocathode Functionalized with a Cobalt Phthalocyanine Molecular Catalyst. Issue 4 (20th December 2022) - Shang, Bo; Rooney, Conor L.; Gallagher, David J.; Wang, Bernie T.; Krayev, Andrey; Shema, Hadar; Leitner, Oliver; Harmon, Nia J.; Xiao, Langqiu; Sheehan, Colton; Bottum, Samuel R.; Gross, Elad; et al.
Abstract: We report a precious‐metal‐free molecular catalyst‐based photocathode that is active for aqueous CO2 reduction to CO and methanol. The photoelectrode is composed of cobalt phthalocyanine molecules anchored on graphene oxide which is integrated via a (3‐aminopropyl)triethoxysilane linker to p‐type silicon protected by a thin film of titanium dioxide. The photocathode reduces CO2 to CO with high selectivity at potentials as mild as 0 V versus the reversible hydrogen electrode (vs RHE). Methanol production is observed at an onset potential of −0.36 V vs RHE, and reaches a peak turnover frequency of 0.18 s −1 . To date, this is the only molecular catalyst‐based photoelectrode that is active for the six‐electron reduction of CO2 to methanol. This work puts forth a strategy for interfacing molecular catalysts to p‐type semiconductors and demonstrates state‐of‐the‐art performance for photoelectrochemical CO2 reduction to CO and methanol. Abstract : A photoelectrode assembly based on planar p‐type silicon and a cobalt phthalocyanine molecular catalyst is developed for photoelectrochemical conversion of carbon dioxide to carbon monoxide and methanol under solar irradiation and in aqueous media.